Trust and Perceived Risks in High School Students' Online Learning Behaviour During Covid19 Pandemic - Sarosa, Samiaji; Setyowati, Agustina Retno (Universitas Nusantara PGRI Kediri, 2022)
This study explores online learning by Indonesian high school students during the Covid19 Pandemic. Many high schools in Indonesia use online learning technology in Google Classroom and Google Meet. The sudden and forced switch from a conventional classroom to a fully online one caught many off guards. This study looks at the behavior of Indonesian high school students in facing sudden changes in study mode from offline or hybrid to full online due to the Covid19 Pandemic. Theory of Planned Behaviour is used and extended by adding Perceived Risks dan Trust to develop a questionnaire. Trust in this study is differentiated between Trust Toward Application and Trust Toward Organization. The survey was distributed to 1986 students from three private high schools in Yogyakarta, Indonesia. As many as 462 responses were received, representing a 23.26% response rate. Data were analyzed using PLS-SEM. The analysis of survey results confirms that TPB, Perceived Risks, and Trust could explain the use of Online Learning by Indonesian high school students. Furthermore, Trust is also influenced, albeit in a small percentage, Perceived Risks.